Rehabilitation and Conservation of Aquatic Resources on Former Nickel Mining Lands - Cahyono, Indra; Nursanti, Evi; Iswanti, Nurul Izza; Hasbir, Muh; Sembor, Yusuf (Indonesian Journal of Coastal and Marine Studies, 2025)
Nickel mining plays a strategic role in supporting the national economy, particularly for the metal and renewable energy industries. However, mining activities also generate significant environmental impacts, especially land degradation and the decline of aquatic resource quality due to increased sedimentation, alterations in the physical and chemical properties of soil and water, and the introduction of heavy metals into aquatic systems. These conditions directly disrupt aquatic ecosystems and reduce biodiversity. This article aims to review rehabilitation and conservation strategies for aquatic resources in post-nickel mining areas through a literature review approach. The study employed a descriptive qualitative method by analyzing relevant national and international scientific publications focusing on land reclamation, revegetation, water quality management, and post-mining aquatic ecosystem restoration. The review results indicate that effective rehabilitation of aquatic resources requires an integrated approach, including land reclamation to stabilize soil conditions, revegetation using adaptive plant species to improve soil fertility and control erosion, and water quality management through sedimentation ponds, constructed wetlands, and riparian vegetation. The implementation of these strategies has been shown to reduce sediment and heavy metal loads, improve water quality, and support the recovery of aquatic ecological functions. Furthermore, community involvement and sustainable management practices are essential to ensure long-term rehabilitation success. With well-planned and sustainable rehabilitation efforts, post-nickel mining areas have the potential to be restored into healthy and productive aquatic ecosystems that provide ecological as well as socio-economic benefits for surrounding communities